ALTERNATIVE FUEL -ENHANCEMENT IN WASTE PLASTIC OIL - Afsana Momin; Anyapanawar R R; Gadwal S.B (International Journal of Innovations in Engineering Research and Technology, 2021)
Recycled fuels have been receiving great attention in order to supply energy recovery especially from waste products. Converting waste product to useful material is a growing interest in fuel research area. Environmental concerns about waste can be eliminated by recycling processes. Plastic pollution can unfavorably affect lands, waterways and oceans. Living organisms, particularly marine animals, can also be affected through entanglement, direct ingestion of plastic waste, or through exposure to chemicals within plastics that cause interruptions in biological functions. Humans are also affected by plastic pollution, such as through the disruption of thethyroid hormoneaxis orhormonelevels.Today our world is increasingly focused on managing waste, recovering energy and protecting the environment. Pyrocrat Systems is committed to these goals and its core expertise is pyrolysis.With the vision of creating better plastic and tire waste management for world, Pyrocrat Systems has developed innovative and robust machinery and technology.Waste plastic disposal and excessive use of fossil fuels have caused environment concerns in the world. Both plastics and petroleum derived fuels are hydrocarbons that contain the elements of carbon and hydrogen. The difference between them is that plastic molecules have longer carbon chains than those in LPG, petrol, and diesel fuels. Therefore, it is possible to convert waste plastic into fuels.